Efforts to Improve Mathematics Learning Outcomes with Ethnomathematics Based Differentiated Learning in Junior High School Students - Mei, Adelvina; Amsikan, Stanislaus; Naimnule, Maria (Program Studi Pendidikan Matematika, Fakultas Ilmu Pendidikan, Universitas Timor, 2025)
This study aims to determine the results of mathematics learning with ethnomathematics-based differentiated learning in grade VII students of Maubeli State Junior High School. This research is called Classroom Action Research, and it was carried out at Maubeli State Middle School. The data collection techniques used are tests and observations. The research instruments used were test questions and observation sheets. The data analysis techniques used are data analysis of test results and analysis of observation data. The results of the study showed that there was an increase in students' mathematics learning outcomes with an ethnomathematics-based differentiated learning approach. The average student learning outcomes and the percentage of class completion from cycle I to cycle II have exceeded the specified standard, namely the average student score reached 68.64 with a classical completion percentage of 64% in the first cycle increasing to 80.52 with a classical completion percentage of 84% in cycle II. Learning with an ethnomathematical approach can increase students' understanding of the material because it is related to the activities they do in their daily lives, especially in the Pancasila Student Profile Strengthening (P5) project